Effects of Paclobutrazol and Uniconazole on the Growth and Development of Syzygium Campanulatum Korth - Mohd Roseli, Ahmad Nazarudin (2006)
Syzygium campanulatum is a perennial indigenous species. It has been widely planted in urban areas as hedge plant, topiary and container planting. This ornamental species requires frequent trimming to maintain its shape due to its vigorous growth. However, the process of pruning or trimming is costly, time consuming and labour intensive. Such a practice may have to be scheduled as frequent as fortnightly to achieve the mentioned purpose, especially in the cases of maintaining the hedge plants and topiaries. Therefore, this study aims to discover an alternative approach in plant maintenance. The main objectives of the study are to determine the effects of plant growth retardants (PGRs) and the optimal dosage for controlling the growth of S. campanulatum for container purposes. This study also aims to determine the effects of PGRs on the appearance of this species after the